PERANCANGAN REBRANDING KINIKO CAFE PADA SOSIAL MEDIA YOUTUBE - ALAN ISRA MIRANDA, Dr. Syafwandi, M.Sn., Elia Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Kiniko cafe rebranding design on youtube social media is a re-promote kiniko cafe in the form of video as the main media, in the video will show the benefits of Kiniko cafe. Aim of this design is to provide information to the general public about Kiniko Cafe. . The method used in data collection is by conducting interviews, observation, and documentation, while the method used to analyze the data is SWOT analysis (Strength, Weakness, Opportunities, and Threats). To strengthen rebranding design Kiniko Cafe is designed various media as supporting media such as x-banner, T-Shirt, mug, totebag, Cd, Cd Box, Cilemek and stickerKeywords : Rebrandinngn, Kiniko Cafe, Social Media, Youtube